Proteasome Activity Profiling Uncovers Alteration of Catalytic β2 and β5 Subunits of the Stress-Induced Proteasome during Salinity Stress in Tomato Roots - Kovács, Judit; Poór, Péter; Kaschani, Farnusch; Chandrasekar, Balakumaran; Hong, Tram N.; Misas-Villamil, Johana C.; Xin, Bo T.; Kaiser, Markus; Overkleeft, Herman S.; Tari, Irma; van der Hoorn, Renier A. L. (Frontiers in Plant Science, 2017)
The stress proteasome in the animal kingdom facilitates faster conversion of oxidized proteins during stress conditions by incorporating different catalytic β subunits. Plants deal with similar kind of stresses and also carry multiple paralogous genes encoding for each of the three catalytic β subunits. Here we investigated the existence of stress proteasomes upon abiotic stress (salt stress) in tomato roots. In contrast to Arabidopsis thaliana, tomato has a simplified proteasome gene set with single genes encoding each β subunit except for two genes encoding β2. Using proteasome activity profiling on tomato roots during salt stress, we discovered a transient modification of the catalytic subunits of the proteasome coinciding with a loss of cell viability. This stress-induced active proteasome disappears at later time points and coincides with the need to degrade oxidized proteins during salt stress. Subunit-selective proteasome probes and MS analysis of fluorescent 2D gels demonstrated that the detected stress-induced proteasome is not caused by an altered composition of subunits in active proteasomes, but involves an increased molecular weight (MW) of both labeled β2 and β5 subunits, and an additional acidic pI shift for labeled β5, whilst labeled β1 remains mostly unchanged. Treatment with phosphatase or glycosidases did not affect the migration pattern. This stress-induced proteasome may play an important role in PCD during abiotic stress.